Clients, Curiosity, and Commitment: A Career in Public Interest Law - Daniel L. Greenberg (Washington University Journal of Law & Policy, 2001)
I want to talk to you about the world of practice. I want to talk to you about school, some of which I know from having spent time not only as a student, but also from running a clinical program in a law school. In the end, I really want to talk about you. What is most important to me concerns the ways in which you can think about a career in public interest, using that term in the broadest possible sense.
Keywords: Legal assistance to the poor; Pro bono legal services; Public interest